Embracing Open Systems Theory Coupled with Methodological Triangulation to Explore The Status of Botswana’s Public Medical Laboratory System Service Delivery - Tapologo Nkoane (Public Health of Indonesia, 2026)
Background: Most resource limited countries experience suboptimal public medical laboratory service delivery which hinders the desirable health care outcomes. Objectives: This study sought to understand issues of suboptimal performance experienced by Botswana’s public medical laboratory system through the application of Open Systems Theory combined with methodological triangulation. Method: A sequential mixed-methods approach was employed to explore the perspectives of Botswana Government–employed medical laboratory scientists working in public medical laboratories within the Greater Gaborone District Health Management Team (GGDHMT) between September 11 and 29, 2023. First, a self-administered questionnaire - adapted from the U.S. President’s Emergency Plan for AIDS Relief (PEPFAR) Site Improvement Through Monitoring System (SIMS) version 4.2 tool - was completed by 16 participants and analysed using Microsoft Excel. Findings from the quantitative questionnaire informed the development of a semi-structured interview guide. Subsequently, two key-informant interviews were conducted, and data was analysed using reflexive thematic analysis. Results: Sixty-five (65) emails were sent to medical laboratory scientists in all the 8 (eight) GGDHMT medical laboratories. Seven (7) emails were “undelivered” resulting in a study sample size of fifty-eight (58).  Response rate of 27.6% % (16/58) was achieved with the following contributions: reference or referral laboratories 11(68%), clinic laboratory 1 (6%) and national quality laboratory contributed 4 (25%). An average of 98% data completeness was achieved, with the online questionnaire achieving (100%) and paper-based questionnaire (91%).  62.5% of participants had a degree or higher qualification, while 68.8% had worked for at least 5 years. The questionnaire identified test interruptions as the main contributor poor laboratory performance. Testing interruptions were attributed to reagents stock-outs 47% (7/15), equipment failure 20% (3/15), expired reagents 20% (3/15), and staff shortage 13% (2/15). The interview identified eight (8) thematic areas:  policy and strategy, equitable funding and support, capacity building, refined workflow, multiplexing, monitoring and evaluation strategy, contract management, equipment standardization Conclusion: Applying Open Systems Theory and a sequential mixed-methods approach revealed critical systemic and operational gaps in Botswana’s public medical laboratory system, highlighting the need to strengthen supply chains, equipment maintenance, workforce capacity, and governance to improve laboratory performance and resilience